2018
DOI: 10.4103/ijo.ijo_1259_17
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intravitreal dexamethasone implant as the first-line treatment for retinal vein occlusion-related macular edema in a real-life scenario

Abstract: Purpose:This study evaluated the effect of intravitreal dexamethasone implant (IDI; Ozurdex) injection for treating macular edema in patients with branch retinal vein occlusion (BRVO) or central retinal vein occlusion (CRVO).Methods:This prospective study included 40 eyes of 40 patients with nonischemic BRVO and 31 eyes of 31 patients with nonischemic CRVO who received IDI injection as the first-line treatment for macular edema. The best-corrected visual acuity (BCVA) value before and after the treatment; intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
(42 reference statements)
2
9
1
1
Order By: Relevance
“…Reid et al [22] showed that the risk of cataract formation is higher in patients receiving multiple IDI injections. Nevertheless, cataract may form because of long-term steroid secretion after a single injection [10]. Meyer and Schönfeld did not reveal any cataract progression at 6 months after intravitreal injection of Ozurdex [23].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Reid et al [22] showed that the risk of cataract formation is higher in patients receiving multiple IDI injections. Nevertheless, cataract may form because of long-term steroid secretion after a single injection [10]. Meyer and Schönfeld did not reveal any cataract progression at 6 months after intravitreal injection of Ozurdex [23].…”
Section: Discussionmentioning
confidence: 87%
“…Simsek et al [10] showed a statistically significant improvement (p < 0.001) of CFT 4 months after intravitreal dexamethasone injection. Moreover, they observed the recurrence of CFT elevation in 65.3% of patients in the BRVO group and in 68.1% in the CRVO group 4 months after the second injection of intravitreal dexamethasone implant.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The article “The efficacy of intravitreal dexamethasone implant as the first -line treatment for retinal vein occlusion-related macular edema in a real-life scenario”[ 1 ] addresses an important question. In this article, the authors have shared their experience with the use of IDI in eyes with macular edema secondary to RVO, which have not received any other prior treatment.…”
mentioning
confidence: 99%